Transformation Of Christian Religious Education With Artificial Intelligence: Building A Spiritual Future In The Digital World - A Dan Kia; Majesty, Gilbert Timothy (International Journal of Christian Education and Philosophical Inquiry, 2025)
Artificial Intelligence (AI) can be a transformational tool in Christian Religious Education in the digital era. Technological advancements bring significant changes to the way we learn and teach, including religious education, which demands innovative methods to remain relevant to the younger generation increasingly connected to technology. AI offers various opportunities to enrich the learning experience and deepen the understanding of Christian values through a more personal and interactive approach. This article discusses several AI applications in Christian religious education, such as virtual assistants for spiritual guidance, in-depth Bible text analysis, and adaptive learning platforms that can tailor materials to the needs of learners. With AI technology, Christian religious education can provide more interactive and responsive modules, allowing learners to delve into religious teachings both individually and in groups. Additionally, the use of AI in analyzing learning behavior allows for more effective curriculum personalization according to the spiritual needs of each individual. This approach can address the challenge of maintaining the relevance of religious values amidst the rapid influx of digital information. This article also examines the potential of AI in aiding faith development, for example through spiritual reflection applications tailored to the user's spiritual growth. This transformation is expected to prepare a generation of Christians who are not only technologically savvy but also spiritually strong, and empowered to face moral and ethical challenges in the future. Thus, AI-based Christian Religious Education can be a pathway to building a relevant and dynamic spiritual future in the digital era.